156k views
1 vote
Helllllllllppppppppppppppppppppppppp meeeeeeeeeeeeeeeeeeeeeee

Helllllllllppppppppppppppppppppppppp meeeeeeeeeeeeeeeeeeeeeee-example-1
User Hammurabi
by
4.7k points

1 Answer

2 votes

Explanation:

You have to substitute the value of the letters in all the expressions:

7.

(6-8)⁵/6-2(-8)² = 16/61

8.

5(-1)² -(-4)² +3/2(-1)-4(-4) = 4/33

9.

-9² -(-6)² +3(-20) = -117

10.

3 |3 -5|² -(3•(-5))² = -213

11.

2(-3)² -5(-3•(-2) -(-2)³ = -4

12.

-(-4)² +7(-2)⁴ -2(-3)³ = 150

User Vilokan Labs
by
5.5k points